Mycoplasma bovis mastitis in dairy cattle - Gelgie, Aga E.; Desai, Sarah E.; Gelalcha, Benti D.; Kerro Dego, Oudessa (Frontiers in Veterinary Science, 2024)
Mycoplasma bovis has recently been identified increasingly in dairy cows causing huge economic losses to the dairy industry. M. bovis is a causative agent for mastitis, pneumonia, endometritis, endocarditis, arthritis, otitis media, and many other clinical symptoms in cattle. However, some infected cows are asymptomatic or may not shed the pathogen for weeks to years. This characteristic of M. bovis, along with the lack of adequate testing and identification methods in many parts of the world until recently, has allowed the M. bovis to be largely undetected despite its increased prevalence in dairy farms. Due to growing levels of antibiotic resistance among wild-type M. bovis isolates and lack of cell walls in mycoplasmas that enable them to be intrinsically resistant to betalactam antibiotics that are widely used in dairy farms, there is no effective treatment for M. bovis mastitis. Similarly, there is no commercially available effective vaccine for M. bovis mastitis. The major constraint to developing effective intervention tools is limited knowledge of the virulence factors and mechanisms of the pathogenesis of M. bovis mastitis. There is lack of quick and reliable diagnostic methods with high specificity and sensitivity for M. bovis. This review is a summary of the current state of knowledge of the virulence factors, pathogenesis, clinical manifestations, diagnosis, and control of M. bovis mastitis in dairy cows.